Programming Languages and Systems 10th Asian Symposium, APLAS 2012, Kyoto, Japan, December 11-13, 2012. Proceedings - Jhala, Ranjit; Igarashi, Atsushi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 10th Asian Symposium on Programming Languages and Systems, APLAS 2012, held in Kyoto, Japan, in December 2012. The 24 revised full papers presented together with the abstracts of 3 invited talks were carefully reviewed and selected from 58 submissions. The papers are organized in topical sections on concurreny, security, static analysis, language design, dynamic analysis, complexity and semantics, and program logics and verification.
Planet Dynamic or: How I Learned to Stop Worrying and Love Reflection -- JATO: Native Code Atomicity for Java -- Ownership Types for Object Synchronisation -- A Functional View of Imperative Information Flow -- End-to-end Multilevel Hybrid Information Flow Control -- Succour to the Confused Deputy: Types for Capabilities -- Types and Access Controls for Cross-Domain Security in Flash -- Linear Approximation of Continuous Systems with Trapezoid Step Functions -- Signedness-Agnostic Program Analysis: Precise Integer Bounds for Low-Level Code -- Hierarchical Shape Abstraction of Dynamic Structures in Static Blocks -- Vinter: A Vampire-Based Tool for Interpolation (Tool Paper) -- Side-Effecting Constraint Systems: A Swiss Army Knife for Program Analysis -- Inference of Necessary Field Conditions with Abstract Interpretation -- Lazy v. Yield: Incremental, Linear Pretty-Printing -- Dynamic Software Update for Message Passing Programs -- A Synchronous Language with Partial Delay Specification for Real-Time Systems Programming -- Concurrent Test Generation Using Concolic Multi-trace Analysis -- Java Bytecode Instrumentation Made Easy: The DiSL Framework for Dynamic Program Analysis -- Indexed Realizability for Bounded-Time Programming with References and Type Fixpoints -- A New Order-Theoretic Characterisation of the Polytime Computable Functions -- A Dynamic Interpretation of the CPS Hierarchy -- Scalable Formal Machine Models -- Modular Verification of Concurrent Thread Management -- A Case for Behavior-Preserving Actions in Separation Logic -- A Generic Cyclic Theorem Prover -- Decision Procedures over Sophisticated Fractional Permissions -- Mechanized Semantics for Compiler Verification.
Keywords: Computer science; Software engineering; Data protection; Logic design; Computer Science; Programming Languages, Compilers, Interpreters; Software Engineering; Logics and Meanings of Programs; Systems and Data Security; Programming Techniques; Mathematical Logic and Formal Languages